Keterkaitan Sifat Sabar dan Optimisme dalam Hadis Nabi: Tinjauan Tekstual dan Kontekstual serta Relevansinya dengan Terapi Self Talk Positif - Rachmat Bin Badani Tempo (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2024)
This research aims to determine the relationship between patience and optimism based on the perspective of the hadith of the Prophet Muhammad. This research is descriptive research using library methods and a ma'ani hadith study approach. The results of this research found several things. First, the Hadith of Abu Hurairah which is the basis of this research is considered valid in terms of sanad and matan. Second, textually, Abu Hurairah's hadith emphasizes the importance of faith, physical strength and enthusiasm in worship and encourages people to be serious in their efforts while asking for Allah's help, and to be patient when facing disaster without saying "if only". Third, contextually this hadith emphasizes the importance of being patient with disasters without saying "if only" because this is contrary to the patient attitude commanded by Allah in the Qur'an so that the value of patience must be reflected in actions and words, as well as avoiding behavior or words that criticize the decrees. God. Fourth, the relevance of this hadith is very strong in everyday life where humans are commanded to try to obtain goodness through hard work, asking Allah for help, and avoiding laziness and weakness. When facing adversity, this hadith teaches the importance of being patient, being kind, and avoiding attitudes that show rejection of Allah's decrees. This research is also in line with modern psychology approaches through positive self-talk therapy, to build an attitude of optimism and a positive mindset in facing life's challenges.